Bridging Usability and Accessibility of User Authentication using Usable Accessed (UAce) for Online Payment Applications - Mohamed, Juliana; Md Fudzee, Mohd Farhan; Ramli, Sofia Najwa; Ismail, Mohd Norasri; Defni, - (JOIV : International Journal on Informatics Visualization, 2021)
Usability and accessibility are significant authentication aspects for online applications. Despite the fact that there are ongoing efforts to improve the interface design, some existing research only focuses on a single aspect of it. Thus, it is vital to investigate how to merge these two features into a practical and workable solution. This study presents a preliminary process for designing accessible and usable applications for online banking payment using Usable Accessed (UAce by adopting Design Science Research (DSR) as its methodology. The UAce standard considers attributes and characteristics from the user authentication. The standard establishes a development method and tool for assessing subjectively and quantitatively usable, as well as the user authentication while taking into account specific elements, qualities, and features. The DSR technique for developing highly usable and accessible interactive apps was utilized in designing this approach.